Conduction Mechanisms in CVD-Grown Monolayer MoS2 Transistors: From Variable-Range Hopping to Velocity Saturation - He, G; Ghosh, K; Singisetti, U; Ramamoorthy, H; Somphonsane, R; Bohra, G; Matsunaga, M; Higuchi, A; Aoki, N; Najmaei, S; Gong, Y; Zhang, X; et al. (Nano letters, 2015)
We fabricate transistors from chemical vapor deposition-grown monolayer MoS2 crystals and demonstrate excellent current saturation at large drain voltages (V d). The low-field characteristics of these devices indicate that the electron mobility is likely limited by scattering from charged impurities. The current–voltage characteristics exhibit variable range hopping at low V d and evidence of velocity saturation at higher V d. This work confirms the excellent potential of MoS2 as a possible channel-replacement material and highlights the role of multiple transport phenomena in governing its transistor action.